Annotated checklist and type catalog of fish genera and species described from Taiwan - Ho, Hsuan-Ching; Shao, Kwang-Tsao (Zootaxa, 2011)
An annotated checklist of fish genera and species described from Taiwanese waters through 2009 is presented. It includes 20 genera and 336 species/subspecies in 99 families. Of these, 225 species/subspecies are currently recognized as valid and 111 are invalid, including 7 questionable species. The current status of each taxon, if different from that of the original description, is provided. Thus far, 41 primary freshwater and estuarine species/subspecies are considered as endemic and 55 marine species are found only around Taiwan. The type series collected from Taiwan are also listed based on the information provided in the original descriptions and from our investigation. It includes approximately 2217 specimens in 779 lots, including 242 holotypes and lectotypes, 5 neotypes, 35 lots of syntypes and 497 lots of paratypes and paralectotypes. There are still 19 species lacking primary types and 11 lots with at least 31 unknown secondary type specimens.